Prevalence of the need for adaptive seating systems among children with cerebral palsy in Egypt. Issue 1 (25th February 2022) - Abdallah, Mohamed Adel; Abdelaziem, Faten; Soliman, Mostafa
Abstract : Background: An adaptive seating system is a basic rehabilitation need for children and youth with cerebral palsy (CP) as it supports the structure and function of the musculoskeletal system and can positively affect their activities and participation. Despite the importance of adaptive seating systems, there is limited access to such systems in low-income countries. Objectives: To determine the percentage of children and youth between 4 and 18 years of age with CP in Egypt whose activity level and sitting ability suggest the need for an adaptive seating system. Study design: Observational cross-sectional study. Methods: One hundred ninety-three participants were included after fulfilling the criteria of the Surveillance of Cerebral Palsy of Europe. Their level of activity was assessed by a physical therapist using the Gross Motor Function Classification System (GMFCS), and their sitting ability was evaluated using the Level of Sitting Scale (LSS). Participants were considered to require an adaptive seating system if they scored GMFCS level IV or V and LSS level 1–5 concurrently. Results: Approximately 44% of the study participants were classified as GMFCS level IV or V and LSS level 1-5, suggesting that they were in need of an adaptive seating system. Conclusions: There is a large percentage of children and youth with CP in Egypt who need an adaptive seating system to be integrated into their rehabilitation.